Study on photodegradation of methyl orange, dimethoate and parathion from aqueous solution by nano iron – manganese oxide particles - Nguyen Vu Ngoc Mai; Nguyen Thi Ha Chi; Duong Thi Lim; Nguyen Quang Trung; Dao Ngoc Nhiem (My University, 2019)
Study on photodegradation of methyl orange, dimethoate and parathion from aqueous solution by nano iron – manganese oxide particles
Keywords: Methyl orange